Bacillus amyloliquefaciens B10 inhibits aflatoxin B1-induced cecal inflammation in mice by regulating their intestinal flora - Chen, Jia; Lv, Zhiming; Cheng, Ziyang; Wang, Tiancheng; Li, Peng; Wu, Aibo; Nepovimova, Eugenie; Long, Miao; Wu, Wenda; Kuca, Kamil (Food and chemical toxicology, 2021)
Aflatoxin B1 is a mycotoxin that widely exists in feed and has a great impact on human and animal health. This study aimed to examine whether Bacillus amyloliquefaciens B10 protected against aflatoxin B1-induced cecal inflammation in mice. It was found that Bacillus amyloliquefaciens B10 could significantly improve the effects of AFB1 on body weight and intestinal inflammation of mice and enhance the expression of tight-junction protein. Compared with the CON group, the combination of AFB1 and B10 significantly increased the abundance of Actinobacteria and Bacilli in a collaborative manner, and significantly reduced the abundance of Ruminococcae, Lactobacillaceae and Clostridia. Meanwhile, the results showed that the abundance of Bacterides and Bacterdia in AFB1 + B10 group was significantly lower than that of AFB1 group, and the Firmicutes increased significantly. Bacillus amyloliquefaciens B10 can be used as a feed additive and alleviate cecal inflammation induced by AFB1 in mice by regulating intestinal flora.
Keywords: Cecum; Animals; cékum; Bacillus amyloliquefaciens; zánět; Male; střevní mikroflóra; aflatoxin B1; Aflatoxin B1; Gastrointestinal Microbiome; mužské pohlaví; myši; zvířata; Inflammation; Mice